H2O2 induced formation of graded composition sodium-doped tin dioxide and template-free synthesis of yolk–shell SnO2 particles and their sensing application - Mikhaylov, Alexey A; Medvedev, Alexander G; Tripol'skaya, Tatiana A; Popov, Victor S; Mokrushin, Artem S; Krut'ko, Dmitry P; Prikhodchenko, Petr V; Ovadia Lev (Dalton transactions : an international journal of inorganic chemistry, 2017)
Sodium peroxostannate nanoparticles with graded composition were produced from aqueous hydrogen peroxide–sodium hydroxostannate solution. The uniform particles were converted to composition graded sodium stannate by mild thermal treatment for peroxide decomposition and yielded yolk–shell tin dioxide particles by dilute acid treatment. The mechanism of formation of the graded sodium concentration is explained in view of the solubility of peroxostannate in H2O2–H2O solution and based on 119Sn NMR, XRD, dynamic light scattering (DLS) and electron microscopy studies. Initial studies illuminating sensitive hydrogen sensing by yolk–shell tin oxide particles are presented.